Non-vascularized large free fibular bone graft in post- traumatic and infectious ulnar bone defect: a case report - Nahar, Kuldeep; Nahar, Nikita (International Journal of Research in Orthopaedics, 2020)
This reported case is about the successful union of an adult male, having open post traumatic infected nonunion of ulna with a bone loss of ulna around 11 cm. Difficult environment around gap nonunion makes the management more difficult for bone graft to stay there. Repeated debridement and skin courage played the key role in controlling the infection. A calculated risk of putting a non-vascular 12 cm autologous fibular graft fixed with plate and screws and supported with medullary nail was taken and a successful union achieved within 4.5 months. So nonvascular free can be a choice for critical bone defects nonunion in fore bones post traumatic one also.